Taking stock of violence in Scotland: final report - Batchelor, Susan (Report, 2019)
Violence is a deeply emotive topic that excites much political and public attention, in Scotland, as elsewhere. It is a source of media fascination and the subject of fiction. Yet violence is a slippery term, with no standard definition, which can take on several different meanings,dependent on the context in which it takes place. Violence, in whatever its variant forms, is widespread. It is experienced in families, in public situations, at work and in people’s treatment of themselves. It is both experienced and used by individuals and by organisations. As a complex phenomenon, its understanding requires the examination of both systemic, situational variables and the dynamics of individual behaviour